The Influence of Corporate Social Responsibility (CSR), Company Size, Leverage and Investment Decisions on Company Financial Performance (Empirical Study of Basic Materials Companies Listed on the Indonesia Stock Exchange 2019-2023) - Riyadi, San San; Winingrum W A, Sri Putri (Journal Of Accounting Management Business And International Research, 2024)
This study aims to determine the influence of corporate social responsibility, company size, leverage and investment decisions on the company's financial performance. This type of research is quantitative and uses secondary data with media in the form of financial and annual company reports in the basic materials sub-sector taken from IDX. The population used in this study is 96 companies through purposive sampling criteria selected 21 samples of companies in the basic materials sub-sector with a period from 2019-2023. Data processing using eviews version 13. Based on the results of the test conducted that simultaneously the variables of influence of corporate social responsibility, company size, leverage and investment decisions have an influence on the company's financial performance.  Partially, corporate social responsibility affects the company's financial performance, the size of the company does not affect the company's financial performance, leverage affects the company's financial performance and investment decisions do not affect the company's financial performance.